Effects of dietary Bacillus NP5 and sweet potato extract on growth and digestive enzyme activity of dumbo catfish Clarias sp. - Achmad Noerkhaerin Putra; Yayu Romdhonah (Jurnal Akuakultur Indonesia)
ABSTRACT